Halal status and society acceptance of edible insects - Palupi, Eny; Uswah, Fathimah; Tanziha, Ikeu; Khomsan, Ali; Setiawan, Budi; Sulaeman, Ahmad; Iwansyah, Ade Chandra; Filianty, Fitri; Muslich, Muslich (IPB University, 2024)
Feeding globally is considered a critical challenge for sustainable development, hence, protein, energy, and adequate micronutrients must be sustainably available to alleviate many community problems. In some parts of Indonesia, such as Gunungkidul, Yogyakarta, approximately 60% of people consume protein less than the adequacy level. Therefore, this study aimed to identify halal status of edible insects as a forgotten-fringe food to obtain a potential alternative source of protein-rich food in the future. The goal was to cover households with lower-middle income in fulfilling protein requirements, specifically in food-insecure areas. The results showed that six edible insects were identified as a forgotten indigenous protein source. These insects were forgotten majorly due to taste (yuck), allergies, inferior quality, complicated processing methods, and confusion over halal status. However, the identified forgotten foods had the potential to cover the insecurity condition in Gunungkidul. This might help poor households increase protein intake since often those forgotten foods are cheap and hunted freely.